2004
DOI: 10.1074/jbc.m402165200
|View full text |Cite
|
Sign up to set email alerts
|

C75, a Fatty Acid Synthase Inhibitor, Reduces Food Intake via Hypothalamic AMP-activated Protein Kinase

Abstract: Energy homeostasis and feeding are regulated by the central nervous system. C75, a fatty acid synthase (FAS) inhibitor, causes weight loss and anorexia, implying a novel central nervous system pathway(s) for sensing energy balance. AMP-activated protein kinase (AMPK), a sensor of peripheral energy balance, is phosphorylated and activated when energy sources are low. Here, we identify a role for hypothalamic AMPK in the regulation of feeding behavior and in mediating the anorexic effects of C75. 5-Aminoimidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
243
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(254 citation statements)
references
References 51 publications
8
243
1
2
Order By: Relevance
“…AMP‐activated protein kinase (AMPK) serves as a cellular energy sensor and is activated in response to a series of metabolic stresses, such as hypoxia, oxidative stress, and glucose deprivation 21, 22. Once activated, AMPK promotes catabolic pathways to generate more ATP, and inhibits anabolic pathways, thus allowing for adaptive changes in growth and metabolism under low energy conditions 23.…”
Section: Introductionmentioning
confidence: 99%
“…AMP‐activated protein kinase (AMPK) serves as a cellular energy sensor and is activated in response to a series of metabolic stresses, such as hypoxia, oxidative stress, and glucose deprivation 21, 22. Once activated, AMPK promotes catabolic pathways to generate more ATP, and inhibits anabolic pathways, thus allowing for adaptive changes in growth and metabolism under low energy conditions 23.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 We and other laboratories have shown that hypothalamic AMPK plays a major role in the regulation of organism's energy balance. [4][5][6] Our interest in hypothalamic AMPK grew from our work with C75, a synthetic molecule that inhibits fatty acid synthase (FAS) 7 and stimulates carnitine palmitoyltransferase-1 (CPT-1) and beta-oxidation of fatty acids. [8][9][10] Fatty acid metabolic pathways are poised at a crossroads of energy deficit and energy surplus, with the potential to either use or make the high-energy molecule ATP.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that C75 increases cellular ATP, and decreases the phosphorylation status and activity of AMPK. 4,8 By increasing the local energy level in energy-sensing hypothalamic neurons, C75 elicits mechanisms that decrease the organism's energy intake and likely also serve to increase wholebody energy expenditure. In our other work, we have also determined that C75 is neuroprotective.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations